Depiction of the goddess Chamunda - Temples of India Project Team (Jio Institute, 2024)
A depiction of the goddess Chamunda is there on the southern wall of the antarala (vestibule or antechamber) of the Hazareshwar Temple. Chamunda, portrayed with twelve arms, stands upon a human body. Skeletal depiction with desiccated breasts and a sunken belly containing a scorpion. She wears a triangular loin cloth to cover her lower body. She has a jatamukuta (crown of matted hair) adorned with a skull at the front. Large earrings dangle from her elongated earlobes, and a snake wraps around her neck and ankles. In her right hand, she holds a trishula (trident), damaru (double-sided drum), arrow, a broken weapon with a staff, and a bell (ghanta). In her left hand, she carries a snake and a broken weapon with a staff. Her left frontal hand holds a bowl, while her right frontal hand touches it. At the bottom left, a human figure is depicted seated, drinking blood dripping from a severed head into a bowl.